Investigations on flow and growth properties of a cavity-actuated supersonic planar mixing layer downstream a thick splitter plate - Li, Hao; Tan, Jianguo; Zhang, Dongdong; Hou, Juwei (The International journal of heat and fluid flow, 2018)
•A cavity is applied as an actuator to improve mixing in supersonic planar mixing layer.•The coherent structures is strongly locked to frequencies from self-sustaining oscillation of supersonic cavity flow.•The normalized growth rate of cavity-actuated supersonic mixing layer is much larger than the typical result of free shear layer.•Curvature shocklets are firstly observed at the low convective Mach number of 0.22. Mixing enhancement is vital to combustion efficiency in a rocket-based combined cycle engine. Presently, we propose a cavity as an actuator and investigate the cavity-actuated supersonic mixing layer experimentally using particle image velocimetry (PIV) and nanoparticle-based planar laser scattering (NPLS). Large eddy simulation (LES) is conducted to obtain the detailed flow structures and pressure spectra of the supersonic mixing layer. Results indicate that the vortex evolution of the supersonic mixing layer is locked strongly to the excitation frequencies from the self-sustaining oscillation of supersonic cavity flow in both the near and far flowfields. Multiple coherent structures of different sizes coexist in the initial flowfields, and then only large ones survive downstream. Pressure spectra can reflect the vortex evolution entirely. The third mode of the pressure spectrum gradually becomes dominant due to having the highest energy content. Curvature shocklets are observed in this case at the low convective Mach number of 0.22. The growth rate in the linear process is slightly larger than that of the case without a cavity while the velocity thickness is 3.34 times as large as that. The normalized growth rate sees a massive increase and is 8.95 times as large as the typical result of a free supersonic shear layer.